Implementation of the Investment Management Framework of National Companies’ Assets - КUCHUKOVA, Nurilya Kenzhebekovna; SHAYAKHMETOVA, Kulshariya Orakpaevna; MADIEVA, Kuralai Sagnaevna; AMIRBEKULY, Yerzhan; UKUBASSOVA, Galiya Sagandykovna; TURSUMBAYEVA, Madina Zhumazhanovna (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
One of the fundamental changes characterizing the restructuring of the Kazakh economy in recent years is the intensive formation of the financial sector, the active development of financial markets as well as the creation of corresponding institutions. Investment remains the most acute problem among the key conditions that determine the course of reforms. The global nature of the investment problem is the need to create a tool for analyzing and forecasting the situation in this area.